On Factor Accumulation and the Pattern of International Specialisation - Bardhan, P. K. (Review of Economic Studies, 1966)
Journal Article On Factor Accumulation and the Pattern of International Specialisation Get access P. K. Bardhan P. K. Bardhan Pembroke College, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 1, January 1966, Pages 39–44, https://doi.org/10.2307/2296639 Published: 01 January 1966